The information needs of people with albinism in Khomas Region, Namibia - Ngula, Anna Kaukowe (Library and Information Studies Centre (LISC), 2019)
The dissertation is a report of an investigation of the information needs of people with albinism in Khomas region, Namibia. The investigation aims to ascertain the information needs of people with albinism (PWA), including the kind of information needs they have. It also seeks to establish the mechanisms used by PWA to seek information and to determine who initiates their information-seeking activities. Furthermore, the study identifies the challenges PWA in Khomas region face on a daily basis when seeking information and recommends information services that could be suitable for PWA in Khomas region. For its theoretical framework, the study applies Moore (2002) and Wilson’s (1996) model of information behaviour. It is situated within the interpretivism paradigm following a qualitative approach. The research design is that of a case study with aspects of autoethnography resulting from the researcher’s personal memory of her lived experiences of albinism as a mother of two children with albinism. Face-to-face interviews were conducted with sixteen people with albinism; six parents of children with albinism (CWA); and two key informants from associations dealing with PWA in Namibia. The findings reveal that PWA have information needs related to their condition, specifically skin and eye care, as well as other basic needs, such as shelter, employment opportunities, education prospects and the process of their acquisition of identity and travel documents. The study revealed that the internet (especially Google), the radio and television, healthcare professionals and Support in Namibia of Albinism Sufferers Requiring Assistance (SINASRA) and Namibia Albino Association Trust (NAAT) are some of the sources and mechanisms used by participants when searching for information. The organisational participants revealed that they provide a range of services to PWA, including information about skin care and protective clothing, as well as applications for disability grants. PWA who participated in the study indicated that they encounter problems when accessing information. These include the long distances between information seekers and providers, time constraints and the cost associated with accessing information. Language was identified as a major barrier to information access because most of the content is in English. Lack of awareness of information sources coupled with poor eyesight for PWA the reading of information in small fonts that is not provided in alternative formats a glaring challenge. The study concluded that information about albinism is critical not only for PWA, but also to an African society that often subjects PWA to grievous harm, simply because it still holds myths and stigma about albinism. Therefore, the study recommends that it is crucial to provide information to PWA, including their family members through platforms such as open days, sensitisation meetings, and the creation of WhatsApp groups. These interventions should also be directed at society at large in order to create a sense of belonging and get rid of isolation suffered by PWA. The study also recommends that an information booklet be developed by the ministry of health and social services. This booklet should contain information on different types of disabilities that can affect unborn children, in order to prepare the parents.